2015
DOI: 10.1111/ane.12518
|View full text |Cite
|
Sign up to set email alerts
|

The structural connectivity of the recurrent transient global amnesia

Abstract: No disruptions in the structural connectivity of the memory pathway were observed in patients with recurrent TGA attacks, refuting the hypothesis that recurrent TGA patients present predisposing weakness of the memory network. The stability of structural connectivity suggests that repeated hippocampal lesions associated with TGA do not affect the microstructure of the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…This is also supported by previous imaging studies that have shown no evidence of structural brain injury after TGA. 40 …”
Section: Discussionmentioning
confidence: 99%
“…This is also supported by previous imaging studies that have shown no evidence of structural brain injury after TGA. 40 …”
Section: Discussionmentioning
confidence: 99%
“…A previous study analyzed the DTI data of 7 patients with recurrent TGA compared to 14 patients with only a single episode of TGA event, and they found the FA and mean diffusivity (MD) were not different between the 2 groups [10]. However, they did not investigate DTI data of the patients with TGA compared to the healthy subjects [10].…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of TGA remains obscure despite extensive research. Several researchers have suggested that the pathophysiologic mechanisms of TGA may be similar to those of cerebral ischemia, epi-DOI: 10.1159/000496511 lepsy, migraine, or a disturbance of venous hemodynamics [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations